John Philip Sousa - Venezia, Mike (2018)
A simple biography of the famous band leader and composer who was known as the March King
Includes bibliographical references and index.
7-9
Keywords: Sousa, John Philip, -- 1854-1932 -- Juvenile literature; Composers -- United States -- Biography -- Juvenile literature